Antigen specific activation of cytotoxic CD8+ T cells by Staphylococcus aureus infected dendritic cells - Friot, Adèle; Djebali, Sophia; Valsesia, Séverine; Parroche, Peggy; Dubois, Maxence; Baude, Jessica; Vandenesch, François; Marvel, Jacqueline; Leverrier, Yann (Frontiers in Cellular and Infection Microbiology, 2023)
Staphylococcus aureus (S. aureus) is a pathogen associated with a wide variety of diseases, from minor to life-threatening infections. Antibiotic-resistant strains have emerged, leading to increasing concern about the control of S. aureus infections. The development of vaccines may be one way to overcome these resistant strains. However, S. aureus ability to internalize into cells – and thus to form a reservoir escaping humoral immunity – is a challenge for vaccine development. A role of T cells in the elimination of persistent S. aureus has been established in mice but it remains to be established if CD8+ T cells could display a cytotoxic activity against S. aureus infected cells. We examined in vitro the ability of CD8+ T cells to recognize and kill dendritic cells infected with S. aureus. We first evidenced that both primary mouse dendritic cells and DC2.4 cell line can be infected with S. aureus. We then generated a strain of S. aureus expressing a model CD8 epitope and transgenic F5 CD8+ T cells recognizing this model epitope were used as reporter T cells. In response to S. aureus-infected dendritic cells, F5 CD8+ T cells produced IFN-γ in an antigen-specific manner and displayed an increased ability to kill infected cells. Altogether, these results demonstrate that cells infected by S. aureus display bacteria-derived epitopes at their surface that are recognized by CD8+ T cells. This paves the way for the development of CD8+ T cell-based therapies against S. aureus.